Customer complaint behaviour of Singaporeans vs. non-Singaporeans in mid-range restaurants : evidence from generation Y customers. - Koh, Chiat Ying. (2009)
The paper aims to investigate the differences in customer complaint behavior and motivation between Generation Y Singaporeans and Non-Singaporeans in Mid-range restaurants. It also takes a deeper delve into the differing cultures of both groups. From there, customer complaint management strategies can be recommended to the restaurant managers.